A cis-eQTL of HLA-DPB1 Affects Susceptibility to Type 1 Autoimmune Hepatitis - Yamazaki, Tomoo (Sci Rep, 2018)
Autoimmune hepatitis (AIH) is a chronic inflammatory liver disease characterized by an autoimmune reaction to hepatocytes. A single nucleotide polymorphism in the 3′ untranslated region of HLA-DPB1, rs9277534, is associated with HLA-DPB1 expression. rs9277534 has been linked to hepatitis B virus recovery/persistence and the risk of graft-versus-host disease with HLA-DPB1 mismatching transplantation of hematopoietic cells, but its role along with that of HLA-DP expression in AIH have not been fully clarified. We genotyped rs9277534 in 146 Japanese patients with AIH and 326 healthy subjects. HLA-DPB1 expression was determined by quantitative PCR. HLA-DPB1 expression was significantly higher for rs9277534G than for rs9277534A (P < 0.05). rs9277534 genotype was in strong linkage disequilibrium with the HLA-DPB1 allele (pairwise D′ = 0.82–1.00). Although HLA-DP alleles were not significantly associated with AIH, the frequency of the rs9277534G allele was significantly higher in AIH patients compared with healthy subjects (P = 0.002, odds ratio [OR] = 1.56). Logistic regression analysis revealed that the HLA-DRB1*04:05 allele (P < 0.001, OR = 4.61) and rs9277534 (P = 0.004, OR = 1.67) were independently associated with AIH susceptibility. rs9277534G in the HLA-DP gene is an eQTL that affects gene expression and may contribute to AIH susceptibility.